Toxic tubular injury in kidneys from Pkd1-deletion mice accelerates cystogenesis accompanied by dysregulated planar cell polarity and canonical Wnt signaling pathways - Happé, Hester; Leonhard, Wouter N.; van der Wal, Annemieke; van de Water, Bob; Lantinga-van Leeuwen, Irma S.; Breuning, Martijn H.; de Heer, Emile; Peters, Dorien J.M. (Human molecular genetics, 2009)
Autosomal dominant polycystic kidney disease (ADPKD) is characterized by large fluid-filled cysts and progressive deterioration of renal function necessitating renal replacement therapy. Previously, we generated a tamoxifen-inducible, kidney epithelium-specific Pkd1-deletion mouse model and showed that inactivation of the Pkd1 gene induces rapid cyst formation in developing kidneys and a slow onset of disease in adult mice. Therefore, we hypothesized that injury-induced tubular epithelial cell proliferation may accelerate cyst formation in the kidneys of adult Pkd1-deletion mice. Mice were treated with the nephrotoxicant 1,2-dichlorovinyl-cysteine (DCVC) after Pkd1-gene inactivation, which indeed accelerated cyst formation significantly. After the increased proliferation during tissue regeneration, proliferation decreased to basal levels in Pkd1-deletion mice just as in DCVC-treated controls. However, in severe cystic kidneys, 10–14 weeks after injury, proliferation increased again. This biphasic response suggests that unrestricted cell proliferation after injury is not the underlying mechanism for cyst formation. Aberrant planar cell polarity (PCP) signaling and increased canonical Wnt signaling are suggested to be involved in cyst formation. Indeed, we show here that in Pkd1 conditional deletion mice expression of the PCP component Four-jointed (Fjx1) is decreased while its expression is required during tissue regeneration. In addition, we show that altered centrosome position and the activation of canonical Wnt signaling are early effects of Pkd1-gene disruption. This suggests that additional stimuli or events are required to trigger the process of cyst formation. We propose that during tissue repair, the integrity of the newly formed Pkd1-deficient cells is modified rendering them susceptible to subsequent cyst formation.